Limitations of Gravimetric Quantitative Blood Loss during Cesarean Delivery - Thurer, Robert L.; Doctorvaladan, Sahar; Carvalho, Brendan; Jelks, Andrea T. (American Journal of Perinatology Reports, 2022)
Objective This study examined the accuracy, sources of error, and limitations of gravimetric quantification of blood loss (QBL) during cesarean delivery.Study Design Blood loss determined by assays of the hemoglobin content on surgical sponges and in suction canisters was compared with QBL in 50 parturients.Results QBL was moderately correlated to the actual blood loss (r = 0.564; p < 0.001). Compared with the reference assay, QBL overestimated blood loss for 44 patients (88%). QBL deviated from the assayed blood loss by more than 250 mL in 34 patients (68%) and by more than 500 mL in 16 cases (32%). Assayed blood loss was more than 1,000 mL in four patients. For three of these patients, QBL was more than 1,000 mL (sensitivity = 75%). QBL was more than 1,000 mL in 12 patients. While three of these had an assayed blood loss of more than 1,000 mL, 9 of the 46 patients with blood losses of less than 1,000 mL by the assay (20%) were incorrectly identified as having postpartum hemorrhage by QBL (false positives). The specificity of quantitative QBL for detection of blood loss more than or equal to 1,000 mL was 80.4%.Conclusion QBL was only moderately correlated with the reference assay. While overestimation was more common than underestimation, both occurred. Moreover, QBL was particularly inaccurate when substantial bleeding occurred.Key Points
Keywords: cesarean delivery; blood loss quantification; postpartum hemorrhage; quality improvement